Efficacy of different spinal orthoses for pain management, functional improvement, and quality of life in osteoporotic vertebral fractures: a mini review - M. B. Borg; M. B. Borg; M. Battaglia; M. Battaglia; M. Invernizzi; M. Invernizzi; A. Baricich; A. Baricich (Frontiers in Rehabilitation Sciences)
Osteoporotic vertebral fractures (OVFs) significantly impair the quality of life in older adults. Spinal orthoses are commonly used, but their effectiveness is debated. Thus, we aimed to evaluate the impact of different spinal orthoses on pain, functionality, and quality of life in patients with OVFs. A review of PubMed, Scopus, PEDro, and Cochrane Library was conducted, covering studies from 2000 to 2024. Studies assessing spinal orthoses’ effects on pain, functionality, and quality of life in adults with OVFs were included. Ten studies involving 970 participants were included. Several studies reported significant improvements in pain, functionality, and quality of life with spinal orthoses. Dynamic hyperextension orthoses, such as Spinomed® and Spinfast®, showed potential benefits, particularly in enhancing trunk muscle strength. In conclusion, spinal orthoses may help manage pain and improve functionality and quality of life in OVFs. However, further high-quality trials are needed to confirm their efficacy.